Metal chelation, radical scavenging and inhibition of Aβ42 fibrillation by food constituents in relation to Alzheimer's disease. (15th May 2016) - Chan, Stephen; Kantham, Srinivas; Rao, Venkatesan M.; Palanivelu, Manoj Kumar; Pham, Hoang L.; Shaw, P. Nicholas; McGeary, Ross P.; Ross, Benjamin P.
Highlights: Studied 9 compounds as chelators, antioxidants, and Aβ fibrillation inhibitors. Developed an assay using 5-Br-PAPS to examine the complexation of Zn(II) and Cu(II). SPLET is the prevailing mechanism of radical scavenging by the polyphenols. Gallic acid, EGCG, and curcumin are multifunctional agents. l -Ascorbic acid and α-tocopherol are potent antioxidants but not multifunctional. Abstract: Various food constituents have been proposed as disease-modifying agents for Alzheimer's disease (AD), due to epidemiological evidence of their beneficial effects, and for their ability to ameliorate factors linked to AD pathogenesis, namely by: chelating iron, copper and zinc; scavenging reactive oxygen species; and suppressing the fibrillation of amyloid-beta peptide (Aβ). In this study, nine different food constituents (l -ascorbic acid, caffeic acid, caffeine, curcumin, (−)-epigallocatechin gallate (EGCG), gallic acid, propyl gallate, resveratrol, and α-tocopherol) were investigated for their effects on the above factors, using metal chelation assays, antioxidant assays, and assays of Aβ42 fibrillation. An assay method was developed using 5-Br-PAPS to examine the complexation of Zn(II) and Cu(II). EGCG, gallic acid, and curcumin were identified as a multifunctional compounds, however their poor brain uptake might limit their therapeutic effects. The antioxidantsl -ascorbic acid and α-tocopherol, with better brain uptake, deserve further investigation for specifically addressing oxidative stress within the AD brain.